Tandem Diboration–Protoboration of Terminal Alkynes: A Practical Route to α-Substituted Alkenyl Boronates - Kong, Ziyin; Park, Jimin; Fei, Muchun; Warfield, Josephine; Wang, Dunwei; Morken, James P. (Synlett, 2024)
A practical method is introduced for the catalytic conversion of terminal alkynes into α-substituted vinyl boronic esters. The process employs catalytic amounts of nanoparticle-supported gold catalysts and catalytic amounts of copper to effect the overall transformation.
Keywords: boron; cross-coupling; AuNPs; alkynes; protonation